Principles of Security and Trust Second International Conference, POST 2013, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2013, Rome, Italy, March 16-24, 2013, Proceedings - Basin, David; Mitchell, John C. (Security and Cryptology, 2013)
This book constitutes the refereed proceedings of the Second International Conference on Principles of Security and Trust, POST 2013, held as part of the European Joint Conference on Theory and Practice of Software, ETAPS 2013, in Rome, Italy, in March 2013. The 14 papers included in this volume were carefully reviewed and selected from 59 submissions. They deal with the theoretical and foundational aspects of security and trust such as new theoretical results, practical applications of existing foundational ideas, and innovative theoretical approaches stimulated by pressing practical problems.